Simulation and modeling of two-level DC/DC boost converter using ARX, ARMAX, and OE model structures - M.A.N. Amran; A.A. Bakar,; M.H.A. Jalil; M.U. Wahyu; A.F.H.A. Gani (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents simulation and modeling of two-level DC/DC boost converter using system identification technique. The main objective is to identify the unknown mathematical model from designated converter that has 2 modes of operation. Signals from the converter were processed based on the impulse response from input and output voltages, which were in time domain data. Auto Regressive with eXogenous (ARX), Auto Regressive Moving Average with eXogenous (ARMAX), and Output-Error (OE) model structure techniques had been employed to generate a model from the converter, whose validation was based on coefficient of determination (R2) or best fits criterion. The result shows that the ARX model structure produced the best model with 94.03%, compared to ARMAX and OE with 93.70% and 92.25% respectively. In terms of stability for open-loop analysis, the ARX model structure gave the most stable system.